2023
DOI: 10.1002/jbt.23619
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin: Nature's promising warrior against Alzheimer's and Parkinson's disease

Ahsas Goyal,
Kunal Solanki,
Aanchal Verma

Abstract: Neurodegenerative disorders (NDs) are defined as the slow loss of a group of neurons that are particularly sensitive. Due to the intricate pathophysiological processes underlying neurodegeneration, no cure exists for these conditions despite the extensive research and advances in our knowledge of the onset and course of NDs. Hence, there is a medical need for the creation of a novel therapeutic approach for NDs. By focusing on numerous signaling pathways, some natural substances derived from medicinal herbs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…Recent studies showed luteolin as a promising warrior against AD ( Goyal et al, 2024 ). In a study by Kou et al (2022) , Luteolin, a naturally occurring flavonoid, demonstrated promising neuroprotective and memory-enhancing effects in a mouse model of AD.…”
Section: Alzheimer’s Disease (Ad)mentioning
confidence: 99%
“…Recent studies showed luteolin as a promising warrior against AD ( Goyal et al, 2024 ). In a study by Kou et al (2022) , Luteolin, a naturally occurring flavonoid, demonstrated promising neuroprotective and memory-enhancing effects in a mouse model of AD.…”
Section: Alzheimer’s Disease (Ad)mentioning
confidence: 99%